Analisis Tax Planning Melalui Natura dan Kenikmatan (kasus PT A) - Dewanto, Dwiyan Bagas; Wijaya, Suparna (Jurnal Ilmiah Akuntansi Kesatuan, 2017)
There are numerous methods of tax planning, one of which is how company runs efficient tax payment which related to tax-saving costs, especially in the form of labors’ benefits in the form of non-cash benefits in kinds allowance. This study is purposed to describe benefits in kinds used as method of tax planning to decrease the amount of tax. The research method used is descriptive qualitative. The result shows that using allowance costs in the form of benefit in kinds can decrease the burden of tax for tax subjects.